Methyl Bromide Fumigation to Eliminate Thousand Cankers Disease Causal Agents from Black Walnut. Issue 4 (20th February 2019) - Seabright, Kendhl W; Myers, Scott W; Fraedrich, Stephen W; Mayfield, Albert E; Warden, Melissa L; Taylor, Adam
Abstract: Phytosanitary treatments for logs and barked wood products are needed to mitigate the spread of thousand cankers disease through the movement of these commodities. The disease threatens eastern black walnut ( Juglans nigra L.) populations in the United States. It is caused by repeated attacks by the walnut twig beetle ( Pityophthorus juglandis Blackman) and subsequent canker development caused by the fungal pathogen Geosmithia morbida M. Kolařík et al. Methyl bromide (MB) fumigations were evaluated for efficacy against P. juglandis and G. morbida in J. nigra bolts. Fumigation with 82 mg/L MB for 24 h at 4.5° C eliminated P. juglandis in J. nigra, but was ineffective against G. morbida. Subsequent experiments focused on eliminating G. morbida, but results were inconclusive because of low rates of pathogen recovery from naturally infested control bolts. Final experiments used J. nigra bolts artificially inoculated with G. morbida. Fumigations with 240 and 320 mg/L MB for 72 h at 10° C were effective in eliminating G. morbida from J. nigra bolts. Results confirm that the USDA fumigation treatment schedule for logs with the oak wilt pathogen will also mitigate the risk of spreading the thousand cankers disease vector and pathogen by movement of walnut bolts and wood products.